Validity Of Overtime Beyond The Established Regulations Based On Employment Agreement At PT TKB - Tasya Destinasari; Ikram, Denial (Universitas Negeri Surabaya, 2024)
This study examines the implementation of overtime work policies at PT TKB, a Food and Beverage company operating in Surabaya, with a focus on the